Equipment for primary check energy meters - Ломако, О.О.; Петрище, М.О.; Шестаков, А.Є.; Трофименко, С.О. (Proceedings of National Aviation University (archive), 2006)
The analysis of an opportunity of automation for carrying out of primary verification of watt-hour meters is lead. Reduction of verification time is theoretically calculated while using specialized verification equipment. Specialized verification installation is developed for carrying out of the absence of a self-feed and a threshold of sensitivity of watt-hour meters. Efficiency of its application is shown at carrying out of primary verification in conditions of a batch production.